2018
DOI: 10.11591/eecsi.v5.1683
|View full text |Cite
|
Sign up to set email alerts
|

Re-Ranking Image Retrieval on Multi Texton Co-Occurrence Descriptor Using K-Nearest Neighbor

Abstract: Some features commonly used to conduct image retrieval are color, texture and edge. Multi Texton Co-Occurrence Descriptor (MTCD) is a method which uses all three features to perform image retrieval. This method has a high precision when doing retrieval on a patterned image such as Batik images. However, for images focusing on object detection like corel images, its precision decreases. This study proposes the use of KNN method to improve the precision of MTCD method by re-ranking the retrieval results from MTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Similar research has also been conducted that discusses the redesign of the image retrieval process using the MTCD and K-Nearest Neighbor (KNN) methods using batik and Corel data. The results of the study showed an increase in the precision of the classification results by 0.8% for batik data and 9% for Corel data [9]. This study shows that MTCD is very well used for processing color and texture extraction for fabric images.…”
Section: Related Researchmentioning
confidence: 69%
“…Similar research has also been conducted that discusses the redesign of the image retrieval process using the MTCD and K-Nearest Neighbor (KNN) methods using batik and Corel data. The results of the study showed an increase in the precision of the classification results by 0.8% for batik data and 9% for Corel data [9]. This study shows that MTCD is very well used for processing color and texture extraction for fabric images.…”
Section: Related Researchmentioning
confidence: 69%